Narracja a tożsamość - przypadek Rolanda Barthes’a - Dziadek, Adam (Przestrzenie Teorii, 2007)
The author makes an attempt at an analysis of the original text „Roland Barthes par Roland Barthes" from the point of view of narration and identity. The fundamental question emerging from the analysis of the text is that of how it is possible to write about oneself at all, writing an autobiography and what obstacles are presented to this kind of writing by language itself and by history. This is proven by unequivocal analyses of personal forms appearing and playing a special role in „RB par RB".